THE ROLE OF GREEN HUMAN RESOURCE MANAGEMENT IN PROMOTING SUSTAINABLE PERFORMANCE: ANALYTICAL STUDY IN THE DORA REFINERY - Tariq Kadhim Shalaka; Radwan Jabbar Goud (Scholar Express Journals, 2022)
The study aims to demonstrate the impact of green human resources management with its dimensions related to (green employment, green performance evaluation, green development and training, green rewards) on sustainable performance with its dimensions of (economic performance, environmental performance, social performance). The study community is represented in the refinery of the session, The sample of the study included managers and heads of departments in the organization, and their number was (38) individuals. To achieve the objectives of the study, the descriptive analytical approach was used. A questionnaire consisting of (28) items was used as a main tool for collecting study data. A number of statistical methods and methods were used to analyze the study variables and test hypotheses, including (arithmetic mean, percentage, standard deviation, coefficient Variation, Pearson correlation coefficient, and structural modeling equation). After conducting a statistical analysis of the study data and its hypotheses, it reached a number of results, most notably the presence of a significant effect of green human resources management in its dimensions on sustainable performance in its dimensions. One of the most prominent conclusions of the study was that the management of green human resources plays a major role in achieving sustainable performance through the degree of interest in the dimensions of the study variables, their interests and applications from the point of view of the study sample members. The study recommended the necessity of enhancing the course management’s interest in green management practices for human resources, setting future plans for adopting green initiatives, spreading a culture of concern for the environment, and showing the green approach in the work environment through workshops and lectures that naturally contribute to achieving sustainable performance for that organization.
Keywords: : Green human resource management; sustainable performance; practices; members